Measurement of Kinetic Friction Coefficient through Magnetic Induction Using Audacity Application in Physics Learning - Rohman, Fatkhur; Azwir, Yohandri; Fauzan, Ahmad (International Journal of Online and Biomedical Engineering (iJOE), 2020)
This study is designed to produce an experimental device for the measurement of the kinetic friction coefficient of material through magnetic induction using Audacity application. The objects of material the kinetic friction coefficient of which is going to be measured is rough acrylic with rough acrylic and wood with rough acrylic. The experimental setup was performed on the motion system of the mass of objects m1 and m2 that were connected through a pulley on a table and three solenoids are put under a table as the Electromagnetic Field (EMF) sensor. Analysis of the calculation of kinetic friction coefficient used two concepts, i.e. the kinematics concept to identify the load acceleration and the concept of the dynamic to find the kinetic friction coefficient. The results of the measurement of kinetic friction coefficient in this study have a match with the results obtained in the other studies. Hence, the tools and experimental approaches generated in this study are excellent for use in the learning activities so that teachers can teach physics applicatively.